2011
DOI: 10.1245/s10434-011-2097-1
|View full text |Cite
|
Sign up to set email alerts
|

TNFAIP8 Overexpression: Clinical Relevance to Esophageal Squamous Cell Carcinoma

Abstract: Our results suggest that TNFAIP8 might be an effective therapeutic target for ESCC in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 12 publications
4
50
0
Order By: Relevance
“…It was originally known as SCC-C2, as it was found in a cell line derived from metastatic head and neck squamous cell cancer and was determined to be a negative regulator of apoptosis in overexpression assays. 17,20,25 Its expression levels correlate with the tumor, node, metastasis (TNM) staging of esophageal squamous cell carcinoma, 26 and a similar pattern has been observed in pancreatic cancer, 27 gastric adenocarcinoma 28 and endometrial cancer. 29 It is also a risk factor for non-Hodgkin's lymphoma, and high levels of TNFAIP8 expression are associated with more aggressive forms of epithelial ovarian cancer with poor survival rates 22,30 as well as with non-small cell lung cancer (NSCLC).…”
Section: Introductionmentioning
confidence: 60%
“…It was originally known as SCC-C2, as it was found in a cell line derived from metastatic head and neck squamous cell cancer and was determined to be a negative regulator of apoptosis in overexpression assays. 17,20,25 Its expression levels correlate with the tumor, node, metastasis (TNM) staging of esophageal squamous cell carcinoma, 26 and a similar pattern has been observed in pancreatic cancer, 27 gastric adenocarcinoma 28 and endometrial cancer. 29 It is also a risk factor for non-Hodgkin's lymphoma, and high levels of TNFAIP8 expression are associated with more aggressive forms of epithelial ovarian cancer with poor survival rates 22,30 as well as with non-small cell lung cancer (NSCLC).…”
Section: Introductionmentioning
confidence: 60%
“…The last exon is common, whereas usage of other exons differs across variants (Supplementary Figure S1). Several reports have shown that TNFAIP8 is overexpressed in human cancers, [3][4][5]8,[19][20][21][22] yet none of these publications have used methods with adequate specificity to discriminate among TNFAIP8 variants. In order to determine the expression patterns of the variants in human tumors compared with normal tissue, we analyzed cataloged RNA-sequencing (RNA-seq) data from primary human tumor and normal tissue for 11 cancer types in The Cancer Genome Atlas (TCGA) (Figure 1a and Supplementary Figure S2A).…”
Section: Resultsmentioning
confidence: 99%
“…The last exon is common, whereas usage of other exons differs across variants (Supplementary Figure S1). Several reports have shown that TNFAIP8 is overexpressed in human cancers, [3][4][5]8,[19][20][21][22] yet none of these publications have used methods with adequate specificity to discriminate among Abbreviations: BrdU, 5-bromo-2'-deoxyuridine; ChIP-seq, chromatin immunoprecipitation sequencing; DOX, doxorubicin; Gadd45A, growth arrest and DNA damageinducible 45a; H3K4me1, histone H3 mono-methylation on lysine 4; H3K4me3, histone H3 tri-methylation on lysine 4; H3K27ac, histone H3 acetylation on lysine 27; p53RE, p53 response element; PCNA, proliferating cell nuclear antigen; Scri, cells expressing scrambled shRNA; shRNA, short hairpin RNA; TCGA, The Cancer Genome Atlas; TNFAIP8, tumor necrosis factor-α-induced protein 8; TP8i, cells expressing TNFAIP8 shRNA …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the possible role of TNFAIP8 in tumorigenesis and its progression, TNFAIP8 overexpression has frequently occurred in several types of cancer tissues and has exhibited clinical relevance (Kumar et al , 2004; Dong et al , 2010; Hadisaputri et al , 2012; Liu et al , 2012; Miao et al , 2012; Zhang et al , 2012, 2013; Shi et al , 2013). As of this writing, no studies on TNFAIP8 in primary EOC tissues have been conducted.…”
mentioning
confidence: 99%